2022
DOI: 10.3390/cancers14092111
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Machine Learning 13-Gene Signature: Improving Risk Analysis and Survival Prediction for Clear Cell Renal Cell Carcinoma Patients

Abstract: Patients with clear cell renal cell carcinoma (ccRCC) have poor survival outcomes, especially if it has metastasized. It is of paramount importance to identify biomarkers in genomic data that could help predict the aggressiveness of ccRCC and its resistance to drugs. Thus, we conducted a study with the aims of evaluating gene signatures and proposing a novel one with higher predictive power and generalization in comparison to the former signatures. Using ccRCC cohorts of the Cancer Genome Atlas (TCGA-KIRC) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 114 publications
(131 reference statements)
0
9
0
Order By: Relevance
“…Gene expression patterns have been shown to improve cancer classification and prediction of patient outcomes, and several groups have developed expression profiling-based molecular tools for ccRCC prognostication ( 5 10 , 40 ). For instance, Rini et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene expression patterns have been shown to improve cancer classification and prediction of patient outcomes, and several groups have developed expression profiling-based molecular tools for ccRCC prognostication ( 5 10 , 40 ). For instance, Rini et al.…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses of the TCGA cohort of ccRCC showed that higher FDX1 expression is significantly associated with longer OS and PFS, and moreover, its downregulation occurs in ccRCC, which collectively indicates that cuproptosis may act as tumor suppressor in this cancer type. Moreover, according to correlation with cuproptosis factors, we identified a panel of cuproptosis-associated genes and developed the CuAGS-13 score model that could predict patient OS/PFS and recurrence risk with a high accuracy.Gene expression patterns have been shown to improve cancer classification and prediction of patient outcomes, and several groups have developed expression profiling-based molecular tools for ccRCC prognostication(5)(6)(7)(8)(9)(10)40).For instance, Rini et al introduced a 16-gene score for recurrence risk stratification in ccRCC patients at stage I -III (10), and Buttner et al set up the S-3 score (the 97 gene signature based on gene expression in the terminal part of proximal tubules) for survival assessment…”
mentioning
confidence: 99%
“…The signature construction used the ceRNA network genes following the methodology of Terrematte and colleagues [94]. The gene signatures were produced using the feature selection techniques in Table S1 and the OmicSelector package (v1.0.0) [95].…”
Section: Dataset Construction Feature Selection and Gene Signature Co...mentioning
confidence: 99%
“…KIRC exhibits significant molecular heterogeneity 4 that involves multiple changes in gene expression. With the help of bioinformatics, a series of key genes associated with renal cancer have been identified as potential biomarkers for diagnosis or survival prediction and as therapeutic targets 5 – 7 . However, since most of these biomarkers are not measured routinely in clinical practice, they are not clinically useful.…”
Section: Introductionmentioning
confidence: 99%